The Portuguese southern maritime border: Genesis, problems and the future of the Selvagens Islands - Graça, P. Q. (New challenges of the Atlantic: An approach from Portugal, 2015)
The movement of strategic reorientation for the sea in Portugal has been given fruits since it was launched almost one generation ago. The proposal for the extension of continental shelf before the United Nations is surely its most significant aspect, and it can been seen that a completely empty space was filled in terms of political discourse and civil society growing consciousness regarding the dimension and potential of the Portuguese sea and the wealth that can be obtained from its biological and geological resources. So, for the moment, although there are more words than actions, Portugal is in a path of responding to the new challenge that the Atlantic poses once again after nine centuries of history. In a historic perspective, the Portuguese are confronted with a dilemma of multiple proportions: Does Portugal need to conjugate the current strategic European option with the historical strategic Atlantic option? Can Portugal do that or is it able to do that? How? Must Portugal chose or is compelled to choose only one of the two?What would be the consequences of that option for Portuguese maritime economy and development? A route into the future of Portugal in theAtlantic Ocean is not possible without solid answers to these questions.